The use of bacterial lysate OM-85 in the treatment of acute respiratory tract infections in children (literature review) - I. A. Dronov; E. A. Kovalenko (Лечащий Врач)
The review is devoted to the analysis of the effectiveness of the use of bacterial lysate OM-85 in the complex therapy of acute respiratory tract infections (ARTI) in children. We analyzed 10 controlled clinical trials, including 7 randomized ones (of which 2 were double-blind, placebo-controlled), which included a total of about 800 patients under the age of 15 years, as well as one observational study, which included 587 children under 12 years of age. In all studies, it was found that the use of bacterial lysate OM-85 in children with ARTI leads to a significantly faster improvement. Also, in some studies, it was shown that the use of this immunostimulant reduces the need for antibiotic therapy and has a pronounced stimulating effect on the immune response: it increases the level of immunoglobulins and interferons, as well as other components of the anti-infective response. Thus, a review of the available scientific publications shows the high efficiency of bacterial lysate OM-85 in the treatment of respiratory infections in children, which makes it possible to recommend the inclusion of this immunostimulant in the complex therapy of ARTI in pediatric practice. At the same time, further clinical studies and generalization of their results in a systematic manner are needed in order to form final conclusions about the therapeutic efficacy of OM-85 bacterial lysate and recommendations for its use.